Development of computer casing using oil palm fibre reinforced epoxy composite - Ham, Kai Wei; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Baharudin, B. T. Hang Tuah (2009)
Malaysia is blessed with abundant and renewable sources of cheap natural fibres, which most of the times are normally regarded as wastes. Oil palm is an example of Malaysian natural fibres that can and are utilized as potential fibres for composites. The main objective of this project is to develop a computer casing from natural fibre reinforced composite using Total Design Method. The design process involved market investigation, product design specification, conceptual design, detail design, and prototyping process. A prototype of the designed product was fabricated using oil palm empty fruit brunch fibre reinforced epoxy. The prototyping process involved fabrication of the composite material, assembly, and surface finishing. Some advantages of natural fibre reinforced computer casing over conventional casings are environmental friendly, renewable, low energy consumption, and significant weight reduction.